Clinical practice guideline for the surgical management of obese adults in the Peruvian Social Security (EsSalud) - Campana-Olazabal, Luis Antonio (2021)
Background: This article summarizes the clinical practice guide (CPG) for the surgical management of obesity in adults in the Social Security of Peru (EsSalud). Objective: To provide clinical recommendations based on evidence for the surgical management of patients with obesity in EsSalud. Material and Methods: A CPG for the surgical managmente of patients with obesity in EsSalud was developed. To this end, a guideline development group (local GDG) was established, including medical specialists and methodologists. The local GDG formulated 7 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in Medline and CENTRAL during 2019. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and the flowchart identification of patients with indication for bariatric / metabolic surgery and selection of the type of surgical intervention. The flowchart was designed in the final phase or last meeting based on the recommendations made previously. Finally, the CPG was approved with Resolution No. 115 – IETSI – ESSALUD – 2020. Results: This CPG addressed 7 clinical questions, divided into topics of surgical management of patients with obesity. Based on these questions, 6 recommendations were formulated (3 strong and 3 conditional), 18 BPC, and 2 flow charts. Conclusion: This article summarizes the methodology, recommendations based on evidence, and the points of good clinical practice from the CPG for the surgical management of obesity in EsSalud.